Crisis management of hotel enterprises in Ukraine based on scenario planning - Iutkina, Alla (Актуальні питання економічних наук, 2025)
The studyʼs relevance is determined by the need to enhance the resilience of hotel enterprises in Ukraine to destabilizing factors by implementing adaptive management strategies. In the context of economic disruptions, military actions, and shifts in consumer segments, applying forecasting methods becomes essential to ensure operational continuity. Scenario-based methods not only allow for assessing the potential impact of external threats but also enable the adaptation of managerial decisions to changing market conditions. The article aims to substantiate approaches to integrating scenario-based methods into the management system of hotel enterprises, considering the specifics of the Ukrainian market. Methods. A systems analysis was used to identify key threats and assess their impact on business operations. Structural and functional analysis was used to determine the main components of management strategies, their flexibility, and effectiveness in conditions of uncertainty. Both methods contributed to a comprehensive assessment of factors affecting operational activities and the development of practical recommendations for adaptation. Results. The study demonstrated that scenario-based methods facilitate timely responses to external changes, optimize management strategies, and mitigate the impact of destabilizing factors. The developed scenarios consider regional specificities, resource constraints, and potential changes in consumer segments, contributing to greater flexibility in managerial decisions. It was found that the main barriers to implementing predictive methods include limited access to relevant data, an insufficient methodological framework, and a low level of digital competence among managers. Using digital platforms to monitor market changes enables timely adjustment of scenarios and prevents potential losses. Conclusions. The feasibility of integrating digital tools for situational monitoring, strategic adaptation, and personnel training has been substantiated. The application of adaptive methods enhances the ability of enterprises to respond quickly to external risks. Further research prospects include the development of models for evaluating the effectiveness of scenario-based methods and integrating machine learning algorithms for market data analysis.